Model Pendidikan Lingkungan Hidup: Kegiatan Pembelajaran pada Siswa Sebagai Bagian dari Lingkungan di Era New Normal - Ferdyan, Rhavy; Vauzia, Vauzia; Zulyusri, Zulyusri; Santosa, Tomi Apra; Razak, Abdul (Natural Science: Jurnal Penelitian Bidang IPA dan Pendidikan IPA, 2021)
This article was written with the aim of discussing the learning ctivity of a model for environmental education in the new normal era. Since COVID-19 hit, environmental issues cannot be separated from the pandemic. There is a need for an environmental education model that was initially blurred and not integrated into the curriculum in schools that is adapted to the new normal era facing the current pandemic. The articles are written using qualitative analysis, observation, and literature study from environmental education documents. The environmental education model in the new normal era is expected to be able to provide understanding and awareness of students as part of the environment and protect it. The environmental education curriculum in the new normal era that needs to be implemented must have achievements where this section discusses education on handling APD (masks) waste that students use, handling hand washing waste, and limiting activities as a form of adaptation to new normal.